Kekosongan Jabatan DPRD Pasca Putusan MK No. 135/PUU-XXIII/2024 - Fernando Binsar Simbolon; Ester Juliana Limbong (CV. ITTC INDONESIA, 2026)
The Constitutional Court Decision Number 135/PUU-XXIII/2024, which separates the implementation of National Elections and Regional Elections, has significant legal implications for the continuity of the tenure of Regional People's Representative Councils (DPRD). The separation of election schedules causes the term of office of the 2024–2029 DPRD members to expire before the regional elections are held in 2031, thereby creating the potential for a vacancy in DPRD positions during the transitional period. This study aims to analyze the legal implications of the DPRD vacancy following the Constitutional Court's decision and to examine alternative solutions from the perspective of constitutional law. The research employs a normative legal method using statutory, conceptual, and case approaches. The findings indicate that there is currently no explicit legal framework governing the mechanism for filling DPRD vacancies during the transitional period, which may lead to legal uncertainty and weaken legislative, budgeting, and supervisory functions at the regional level. Therefore, policy reform through amendments to the Election Law is necessary to ensure legal certainty, maintain the continuity of regional governance, and uphold the principles of popular sovereignty and constitutional democracy.